A Return to the Picturesque: Reading the Landscape in Lettie Viljoen's Landskap met vroue en slang - Human, Thys (Journal of literary studies (Pretoria, South Africa), 2010)
In Landskap 1 met vroue en slang (Landscape with Women and Snake) (1996) - the last novel published under Ingrid Winterbach's pseudonym Lettie Viljoen - the main character, Lena Bergh, relocates with her husband from Stellenbosch to Durban. As a result she suddenly finds herself in a lush, subtropical landscape that does not inspire her as a visual artist, but rather confuses and overwhelms her. Because of her psychological discontent, Lena deeply yearns for the familiar, soothing landscape of the Western Cape that she had to leave behind. She becomes so obsessed with her past in the Cape that she cannot succeed in continuing her life (or role as artist) in Durban with enthusiasm. One thing that stimulates Lena's interest, however, is the reading she does of the so-called sublime landscapes of the Baroque painter, Nicolas Poussin, especially his landscape cycle "The Four Seasons" (1660-1664). This article investigates the relationship between Lena's obsession with the past, the problems she is experiencing in adapting to the subtropical coastal landscape of Durban and the loss of creative focus and inspiration that she experiences as visual artist. Specific attention is given to the way in which Lena's reading of the so-called sublime landscape - and especially the pictorial and compositional aspects of Poussin's landscapes - eventually enables her to observe the surrounding landscape in a new way and to get a certain (artistic) grip on it. Finally, it is indicated that the picturesque principles suggested by Poussin's landscape cycle do not only afford Lena the visual apparatus to appreciate the surrounding Natal landscape, but also offer the reader of Viljoen's text certain artistic principles according to which the novel can be read and interpreted as sublime landscape. 1 In her first five novels the novelist and artist Ingrid Winterbach used the pseudonym Lettie Viljoen. Winterbach has been described by critics as "one of the most original novelists" (Viljoen 2007: Cover Review), "one of the most interesting writers in Afrikaans" (Krog 2005: Cover Review) and as "an essential voice" (Krog 2007: Cover Review). She has been honoured with numerous awards, including the M-Net Book Prize (1994 & 2007), the Old Mutual Literary Prize (1997), the W.A. Hofmeyer Prize (2000 & 2007), the Hertzog Prize (2004) and the UJ Creative Writing Prize (2007). Yet she remarks in an interview (de Vries 2007) that her work has largely gone unnoticed by most English-speaking readers. The translation into English of Karolina Ferreira (The Elusive Moth, 2005), Niggie (To Hell with Cronjé, 2007) and Die boek van toeval en toeverlaat (The Book of Happenstance, 2008) will hopefully change this, however.